Cross-Country Connectedness in Inflation and Unemployment: Measurement and Macroeconomic Consequences - Binh Thai Pham; Hector Sala (Institute of Labor Economics (IZA), 2021)
We bring the notion of connectedness (Diebold and Yilmaz, 2012) to a set of two critical macroeconomic variables as inflation and unemployment. We focus on the G7 economies plus Spain, and use monthly data –high-frequency data in a macro setting– to explore the extent and consequences of total and directional volatility spillovers across variables and countries. We find that total connectedness is larger for prices (58.28%) than for unemployment (41.81%). We also identify asymmetries per country that result in higher short-run Phillips curve trade-offs in recessions and lower trade-offs in expansions. Besides, by exploring time-varying connectedness (resulting from country-specific shocks), we find that volatility spillovers magnify in periods of common economic turmoil such as the Global Financial Crisis. Our results call for an enhancement of international macroeconomic policy coordination.
Keywords: C32; C50; E24; F41; F42; 330; country-specific shocks; connectedness; Philips curve; G7; common shocks